Evaluation of surgical wound healing in orthopedic patients with impaired tissue integrity according to nursing outcomes classification (2018)
ABSTRACT: PURPOSE: To assess the surgical wound (SW) healing in orthopedic patients with Impaired tissue integrity according to the Nursing Outcomes Classification (NOC). METHODS: A prospective longitudinal study performed with 24 patients. Data collection was performed through an instrument containing the NOC indicators. FINDINGS: The indicators skin approximation, drainage, surrounding skin erythema, periwound edema, increased skin temperature, and foul wound odor presented a statistically significant increase when compared the means between the first and the last day of evaluation. CONCLUSION: The NOC indicators allowed to monitor the SW healing indicating an improvement. IMPLICATIONS FOR NURSING PRACTICE: The NOC can favor an earlier identification of the degree of commitment for each patient and enables implementation of care to achieve target outcomes.